IMPACT OF TUMOR CHARACTERISTICS AND TREATMENT ON SURVIVAL OUTCOMES IN PEDIATRIC KIDNEY TUMORS (Herald of the National Children's Medical Center, 2025)
Renal tumors are among the most common malignancies in pediatric oncology, necessitating tailored treatment approaches to improve survival outcomes. This study aims to identify prognostic factors influencing survival in children with kidney tumors treated at a tertiary-level hospital in Tashkent, Uzbekistan.